If x + y = 6, then solve for y to get: y = 6 - x.
Now replace y with 6 - x in both equations.
(5x)/3 + 6 - x = c
2(6 - x) = c - 4x
The upper equation is solved for c.
Now we solve the lower equation for c.
c = 2(6 - x) + 4x
c = 12 - 2x + 4x
c = 2x + 12
Since we have two equations solved for c, we substitute to get
(5x)/3 + 6 - x = 2x + 12
This is an equation in only x, so we can solve for x.
(5x)/3 - 3x = 6
5x - 9x = 18
-4x = 18
x = -9/2
Now we solve for y.
x + y = 6
-9/2 + y = 6
y = 9/2 + 12/2
y = 21/2
Now we solve for c.
c = (5x)/3 + y
c = (5 * (-9/2))/3 + 21/2
c = -45/6 + 21/2
c = -15/2 + 21/2
c = 6/2
c = 3
Answer: c = 3
He planted D. 29,928 Bulbs
First Add up all the bulbs.
Then multiply the # of bulbs with the # of fields.
Answer:
4 14/15 more pounds of roast beef
Step-by-step explanation:
subtract 4 2/3 from 9 3/5
9 3/5 - 4 2/3= 4 14/15
So your answer is 4 14/15
Answer:
2 11/12
Step-by-step explanation:
(1/3)×(35/4=35/12=2 11/12 yards
4/7 is the simplest form
You can divide 20 by 5 and get 4 and divide 35 by 5 and get 7